Decapod larvae distribution and species composition off the southern Portuguese coast. (1st December 2017) - Pochelon, Patricia N.; Pires, Rita F.T.; Dubert, Jesús; Nolasco, Rita; Santos, A. Miguel P.; Queiroga, Henrique; dos Santos, Antonina
Abstract: For decapod crustaceans, the larval phase is the main responsible for dispersal, given the direct emission from adult habitats into the water column. Circulation patterns and behavioural mechanisms control the dispersal distance and connectivity between different areas. Information on larval distribution and abundance is required to predict the size and location of breeding populations, and correctly manage marine resources. Spatial distribution and abundance data of decapod larvae, and environmental parameters were assessed in winter surveys off the southern Portuguese coast. To better understand the oceanic structures driving larval distribution patterns, in situ physical parameters were measured and a hydrodynamical model used. Inter-annual, cross-shore and alongshore differences on decapod larvae distribution were found. Brachyuran crabs dominated the samples and similar taxa composition was observed in the most dynamic areas. Coastal taxa dominated the nearshore survey and were almost absent in the more offshore one, that registered much lower abundances. An upwelling front allowed a clear cross-shore species separation, also evident in the abundance values and number of taxa. Hydrodynamical conditions and adult habitats were the main factors explaining the observed patterns. Important missing information to understand the distribution patterns of decapod larval communities and the mechanisms behind them is given for the region. Highlights: Spatial distribution and abundance of decapod larvae were assessed for the southern Portuguese coast. The retention/dispersal mechanisms are explored for winter periods. Inter-annual, cross-shore and alongshore differences in distribution were found. Hydrodynamic conditions, shelf characteristics and adult habitats influenced the observed patterns. Important missing information on distribution patterns is given for the area.